Canva-Supported Economics Instruction and the Development of Learning Interest among Senior High School Students - Jurana Ambo Asse; Sahiruddin; Muhammad Yany (Yayasan Ahmar Cendekia Indonesia, 2026)
This study aimed to analyze the effect of using the Canva application as a learning medium on the learning interest of tenth-grade students in Economics at SMA Negeri 15 Bone. The study employed a quantitative approach using an ex post facto research design. The population consisted of 373 tenth-grade students, while a sample of 50 students was selected through simple random sampling. Data were collected using questionnaires and documentation and analyzed through descriptive statistics and simple linear regression with the assistance of IBM SPSS Statistics Version 26 after fulfilling the prerequisite tests, including normality, linearity, and heteroscedasticity tests. The findings revealed that the use of the Canva application significantly influenced students' learning interest. The regression equation obtained was Y = 15.640 + 0.781X, indicating that every one-unit increase in the use of Canva was followed by a 0.781-unit increase in students' learning interest. The results suggest that the use of Canva as a learning medium contributes to creating a more engaging learning environment, facilitates the presentation of learning materials, and enhances students' interest in participating in Economics learning. Therefore, Canva can serve as an effective digital learning medium to support the improvement of students' learning interest.